Cognitive security: A comprehensive study of cognitive science in cybersecurity. (October 2019) - Andrade, Roberto O; Yoo, Sang Guun
Abstract: Nowadays, IoT, cloud computing, mobile and social networks are generating a transformation in social processes. Nevertheless, this technological change rise to new threats and security attacks that produce new and complex cybersecurity scenarios with large volumes of data and different attack vectors that can exceeded the cognitive skills of security analysts. In this context, cognitive sciences can enhance the cognitive processes, which can help to security analysts to establish actions in less time and more efficiently within cybersecurity operations. This works presents a cognitive security model that integrates technological solutions such as Big Data, Machine Learning, and Support Decision Systems with the cognitive processes of security analysts used to generate knowledge, understanding and execution of security response actions. The model considers alternatives to establish the automation process in the execution of cognitive tasks defined in the cyber operations processes and includes the analyst as the central axis in the processes of validation and decision making through the use of MAPE-K, OODA and Human in the Loop.